Presentation - Publishers (Farol, 2024)
Welcome to edition 29 of Farol. This issue presents a thematic dossier curated by André Arçari and Bruno Zorzal. Under the title “Wrath of images: control, resistance, war”, we find nine works that range between articles and textual and visual essays. With sharp and diverse views, these works provide us with an in-depth reading about the interconnections between the works, emerging trends and the challenges faced in thinking about the production and presence of images in photography, video and cinema. Based on the production of filmmaker Harun Farocki, we enter into debates about the devices that direct the images of our world in constant conflict.